1991
DOI: 10.1073/pnas.88.17.7763
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium rhizogenes pRi8196 T-DNA: mapping and DNA sequence of functions involved in mannopine synthesis and hairy root differentiation.

Abstract: This paper presents the map and DNA sequence analysis of pRi8196 transferred DNA (T-DNA) genes encoding root-inducing and mannopine synthesis functions. A canonical 24-base-pair border repeat as well as two "pseudoborders" are present at the functional right T-DNA border. To the left of this border are homologs ofthe masi' and mas2' genes of TR pRiA4. Next to these are five open reading frames (ORFs) homologous to ORFs 1-14 of TL of pRiA4. ORFs 10-12 (roL4, roWl, and roi) are less related to their pRiA4 homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 42 publications
(43 reference statements)
0
44
0
Order By: Relevance
“…11). rolB homologues of strains of A. rhizogenes other than the agropinetype strain also have coding regions longer than that of the NgrolB gene (28)(29)(30). Although the ORF of NgrolB starts at the corresponding base of RirolB, differences in bases at sites 633 and 723 bp from the initiation codon generate early-termination codons.…”
Section: Molecular Evolutionary Analysismentioning
confidence: 99%
“…11). rolB homologues of strains of A. rhizogenes other than the agropinetype strain also have coding regions longer than that of the NgrolB gene (28)(29)(30). Although the ORF of NgrolB starts at the corresponding base of RirolB, differences in bases at sites 633 and 723 bp from the initiation codon generate early-termination codons.…”
Section: Molecular Evolutionary Analysismentioning
confidence: 99%
“…Nor do these bacteria express mannopine cyclase activity. The T region of one mannopine-type Ri plasmid contains close homologs of the mas1 and mas2 genes found on the T region of agropine-type Ri and Ti plasmids but lacks ags (13). Thus, the opine biosynthesis systems specified by the mannopine-and agropine-type T-DNAs differ only by the presence of ags.…”
Section: Figmentioning
confidence: 99%
“…It was found that the right T-DNA (T R -DNA) contains genes homologous to T-DNA of A. tumefaciens Ti plasmid (Huffman et al 1984;Jouanin 1984;Vilaine and CasseDelbart 1987;Hansen et al 1991;Chandra 2012). Among them, the most important genes are those homologous to the tms1 and tms2 of the Ti-plasmid.…”
Section: T R -Dnamentioning
confidence: 99%
“…Since these strains are still capable to induce a "hairy-root" phenotype, it can be said that the presence of the aux genes on T R -DNA is not necessary to generate hairy root phenotype. It has been demonstrated that the aux genes are required to support the "hairy root" phenotype and to extend the host range of the bacterium Cardarelli et al 1987b;Hansen et al 1991;Sevon and OksmanCaldentey 2002).…”
Section: T R -Dnamentioning
confidence: 99%